Bioactive 2-(methyldithio)pyridine-3-carbonitrile from Persian shallot (Allium stipitatum Regel.) exerts broad-spectrum antimicrobial activity - Karunanidhi, Arunkumar; Ghaznavi-Rad, Ehsanollah; Jeevajothi Nathan, Jayakayatri; Sither Joseph Vesudian, Narcisse Mary; Chigurupati, Sridevi; Mohd Fauzi, Fazlin; Pichika, Mallikarjuna Rao; Awang Hamat, Rukman; Than, Leslie Thian Lung; Van Belkum, Alex; Neela, Vasantha Kumari (MDPI, 2019)
Antibiotic resistance is a problem that continues to challenge the healthcare sector, especially in clinically significant pathogens like methicillin-resistant Staphylococcus aureus (MRSA). Herein is described the isolation and structure elucidation of a bioactive compound from Allium stipitatum with antimicrobial activity. Crude Allium stipitatum dichloromethane extract (ASDE) was subjected to systematic purification by chromatographic procedures to afford various bioactive fractions. A fraction that exhibited anti-MRSA activity (4 µg·mL−1) was further characterized to determine the structure. The structure of the compound was elucidated as 2-(methyldithio)pyridine-3-carbonitrile (2-Medpy-3-CN). The 2-Medpy-3-CN compound, which was screened for antimicrobial activity, exhibited minimum inhibitory concentrations (MICs) in the range of 0.5 to >64 µg·mL−1 for tested bacterial species and 0.25 to 2 µg·mL−1 for Candida spp. Further studies are important to confirm the drug target and mechanism of action.